Sosialisasi Perencanaan Keuangan dan Investasi bagi Masyarakat Pesisir Laut Negeri Hukurila - Laury M. Ch. Huwae; Ronald D. Hukubun; Kesia L. Sahusilawane; Hermanto Romera; Hendrikus Sakliressy; Sherly Lewerissa (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
In the national economy, tourism is a sector that is expected to improve the economy as a whole. The tourism sector has an important role as a source of foreign exchange earnings, and can encourage national economic growth, especially in reducing the number of unemployed and increasing the productivity of a country. Moreover, Hukurila itself has tourism potential and sea potential which, if managed properly, can increase income for the community. And for that financial planning is needed to manage finances in the future so that they are neatly organized and from this income people can save their money or invest in the capital market in order to get long-term benefits.